Adoption of Moth Bean Production Technology in Arid Zone of Rajasthan - Singh, Bhagwan; Chauhan, T R (Annals of Arid Zone, 2016)
The study was conducted in two panchayat samities of Jodhpur district of Rajasthan. From each panchayat samiti three villages and from each village 30 farmers, 10 each with marginal, small and large holdings were selected randomly. Majority of the marginal, small and large farmers belonged to low adoption category for the practices such as high yielding varieties. seed treatment, application of nitrogenous fertilizers. application of phosphatic fertilizers and plant protection measures, medium adoption for the practices like time of sowing, application of organic manure and interculture and weeding and high adoption for the practices such as seed rate, method of sowing and spacing of moth bean production technology. Age of the marginal, small and large farmers was negatively and significantly correlated with extent of adoption of moth bean production technology while education, mass media exposure. contact with extension agencies and infrastructure facilities were positively and significantly correlated with adoption. Key words: Adoption, seed treatment, plant protection measures.